The Illusion of Transparency: Analyzing ‘The Circle’ as a Critique of Social Media’s Role in Shaping Digital Identities and Cultural Expression - Sangeetha J (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Social media has transformed from just a basic communication tool into a major force for cultural expression and identity creation, changing how people and communities connect, perform, and define themselves in our digital world. This research delves into how Dave Eggers’ novel, The Circle, critiques the overwhelming influence of social media platforms on individual identities and cultural expression. The story paints a dystopian picture of a society stripped of privacy, where personal lives are under constant watch, reflecting the social media-driven reality we face today. By examining the narrative and characters in The Circle, this paper investigates how social media platforms provide avenues for self-representation while also commodifying and distorting personal identity. Through the character of Mae Holland, who gradually loses her independence as she dives deeper into the Circle’s ideology of complete transparency, the research draws connections to how actual social media platforms promote identity performance for public viewing. By engaging critically with the novel, this study highlights the repercussions of a culture that values visibility and engagement over privacy and authenticity, offering valuable insights into the intricate relationship between digital spaces, cultural expression, and personal identity.